Rheological properties of crude oils in Yaregskoye and Yaraktinskoye oil fields; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Manzhai V. N. Vladimir Nikolaevich (Petroleum Geology: Current Exploration and Extraction Methods, 2016)
Title screen